An accurate technique for supervising distance relays during power swing - Loai Mohamed Ali El-Sayed; Doaa Khalil Ibrahim; Mahmoud Ibrahim Gilany; Aboul’Fotouh El’Gharably (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Power swing is a power system transient phenomenon that arises due to several reasons including line switching, line outage, sudden increment or decrement in load, faults, etc. Unnecessary tripping during power swing and unnecessary blocking for faults occur during power swing result in distance relay maloperation. Several cascaded outages and major worldwide blackouts have occurred due to maloperation of distance relays. This paper proposes a technique for supervising distance relays during power swing. The proposed online technique discriminates real faults and power swing accurately. It relies on constructing a locus diagram for the current and voltage differences (∆I-∆V) between the two ends of the protected line. The locus is estimated at every power frequency cycle to continuously monitor the state of the line by utilizing the synchrophasor measurements at the sending and receiving ends of the line. The proposed technique is tested for two-area, four-machine power system under faults at different locations of zone-1 and zone-2 regions of distance relays, fault resistances, fault inception angles and slip frequencies using MATLAB software. The simulation results proved the superior improvement of distance relay performance for handling power swing blocking and unblocking actions.